2004
DOI: 10.1002/ange.200461092
|View full text |Cite
|
Sign up to set email alerts
|

Tunable, Superhydrophobically Stable Polymeric Surfaces by Electrospinning

Abstract: The high water repellence of superhydrophobic surfaces is attributed to the limited contact area between the solid and water which is manifested by a high static water contact angle (WCA) and a low sliding angle. The solid-liquid interfacial energy can be minimized by engineering not only the chemistry but also the topography of the solid surface. [1,2] For example, epicuticular wax on the lotus leaf is an intrinsically hydrophobic material.[3] However, when nano-sized crystals of wax cover a micron-level roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…However, when the size of SiO 2 nanoparticles was increased to 150 nm, the WCA was decreased drastically to 124 • . On the other hand, Karapanagiotis et al [52] used Al 2 O 3 nanoparticles with different sizes (25,35, and 150 nm) in their coatings, and they found that the coating wettability is independent of the size of the nanoparticles. Then, in a more recent study, they [53] found an effect for the size of the nanoparticles on the wettability of their coatings, only if the concentration of the nanoparticle is high.…”
Section: Wettabilitymentioning
confidence: 99%
“…However, when the size of SiO 2 nanoparticles was increased to 150 nm, the WCA was decreased drastically to 124 • . On the other hand, Karapanagiotis et al [52] used Al 2 O 3 nanoparticles with different sizes (25,35, and 150 nm) in their coatings, and they found that the coating wettability is independent of the size of the nanoparticles. Then, in a more recent study, they [53] found an effect for the size of the nanoparticles on the wettability of their coatings, only if the concentration of the nanoparticle is high.…”
Section: Wettabilitymentioning
confidence: 99%
“…In addition to the above, electrospinning is also a predominant and promising technique to develop superhydrophobic surfaces from some polymers with low surface energies and introducing the hierarchical structure to them. In recent years, several types of superhydrophobic surfaces, produced by electrospinning of PVDF, have been reported in the literature [21][22][23][24][25][26]. Additionally, it will be a good task to obtain a kind of novel film with PVDF/graphene electrospun thin layers coated on the surface of porous supports like polypropylene (PP) and polytetrafluoroethylene (PTFE).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13]15] To mimic the topography of the lotus leaf and to achieve a high WCA, we fabricated a polymeric film surface with a high degree of roughness through a simple and practical electrospinning process. [16] Electrospun films consist of a continuous, nonwoven web of fibers (with diameters in the order of 1-1000 nm) and, depending on processing conditions, with polymer droplets either as isolated spheres (> 1 mm in diameter) or strung along a fiber. [17][18][19][20][21][22] The electrospun film is produced by applying an electrical bias from the tip of a polymer solution-filled syringe to a grounded collection plate.…”
mentioning
confidence: 99%